Estudio de las medidas de seguridad en la red GPON de CNT-EP en la zona 1, sector Cerro Santa Ana de la Ciudad de Guayaquil - Santillán Villota, Cesia Jemima (2021)
The National Telecommunications Corporation - EP offers connectivity services to users through GPON technology in Cerro Santa Ana in the City of Guayaquil. The purpose of this research is to study the security measures of the aforementioned network, due to the age they present, being the bases for the expansion of GPON technology to other areas of the city, the lack of physical maintenance and the large volumes that are transmitted over the fiber cable can make them attractive targets for malicious people, causing vulnerabilities to exist both at a logical and physical level. The methodology that was used in the development of the research is quantitative, the same that with the help of the interview as a technique and the questionnaire as an instrument allowed to carry out the respective analysis, to determine that the company has not established specific vulnerabilities in the networks GPON and it is unknown that it has security measures, however it is considered important that these exist and that the technicians would be willing to be trained regarding the vulnerabilities and common threats that may exist in the GPON network.